Paracoccidioidomicose em paciente com carcinoma do colo uterino Paracoccidioidomycosis in a patient with cervical cancer - Silvio Alencar Marques; Joel Carlos Lastória; Mariangela Esther Alencar Marques (Sociedade Brasileira de Dermatologia, 2011)
Os autores relatam caso de paciente do sexo feminino com paracoccidioidomicose, associada a carcinoma do colo uterino estádio IIIB. Paracoccidioidomicose, associada à neoplasia, ocorre entre 0,16% a 14,1% segundo diferentes séries de casos. Em casos com neoplasia disseminada a infecção fúngicas pode apresentar comportamento oportunístico This report describes the case of a female patient with paracoccidioidomycosis associated with a stage IIIB cervical carcinoma. Paracoccidioidomycosis in association with a malignant tumor occurs in 0.16% to 14.1% of cases in accordance with different case series. In cases in which the cancer is disseminated, the fungal infection may behave opportunistically